Epidemiologic and Genotypic Distribution of Noroviruses Among Children With Acute Diarrhea and Healthy Controls in a Low-income Rural Setting. (23rd October 2018) - Hossain, Mohammad Enayet; Rahman, Rajibur; Ali, Sk Imran; Islam, Md Muzahidul; Rahman, Mohammed Ziaur; Ahmed, Shahnawaz; Faruque, Abu Syed Golam; Barclay, Leslie; Vinjé, Jan; Rahman, Mustafizur
Abstract: Background: Noroviruses are the most common cause of epidemic and endemic acute gastroenteritis (AGE) worldwide. The burden of norovirus disease in low-income settings is poorly understood. Methods: We tested stool samples from children less than 5 years of age with diarrhea who were admitted in a rural hospital in Bangladesh from 2010–2012 and from matched, healthy controls from the same catchment area. Results: Norovirus was detected in 109 (18%) of 613 children with diarrhea and in 30 (15%) of 206 healthy controls. Most (n = 118; 85%) norovirus infections belonged to genogroup II (GII). Of these, GII.4 viruses were identified in 36 (33%) of the cases and in 6 (21%) of the controls. Other major genotypes included GII.3 (13%), GII.6 (11%), and GII.13 (11%) in the cases and GII.6 (17%) and GII.2 (14%) in the controls. The greatest risk of severe norovirus disease (Vesikari score ≥11) was associated with GII.4 infections. GII.4 viruses were the predominant genotype detected during the winter (55%) and rainy season (23%), while GII.3 (19%) and GII.13 (19%) viruses were the most prevalent genotypes during the summer. Vomiting was significantly associated with GII.4 infections, while longer durations of diarrhea were associated with GI.3 infections. Conclusions: Future studies are needed to understand the high rates of virus shedding in children without AGE symptoms. Abstract : Norovirus was identified as a key cause of acute diarrhea in children <5 years of age; however, the prevalence and genotype distribution were almost similar to age-matched healthy controls. Genotype II.4 caused higher disease severity than other norovirus genotypes.